the PENATALAKSANAAN FISIOTERAPI PADA PENDERITA GANGGUAN NYERI AKIBAT SINDROM PIRIFORMIS DENGAN TEKNIK STRAIN COUNTERSTRAIN DAN CONTRACT RELAX STRETCHING DI KELURAHAN PEKAPURAN RAYA KOTA BANJARMASIN - NAFI'AH NAFI'AH (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2019)
Continuous use of muscles can may caused hyperactively muscle activity which eventually induced pain and muscle spasm in the lower back area to the backside. In addition, muscle spasm may lead pressure on the nerves to generated swelling, inflammation, and symptoms of nerve irritation. One of the nerve irritations that often results from muscle spasm is piriformis syndrome. Piriformis syndrome is a musculoskeletal condition characterized by pain in the waist, lower back to the backside upper lower limbs that results from shortening or spasm piriformis obtained compression of the sciatic nerve. As a result of these problems, the authors conducted a study to determine the management of physiotherapy using Strain Counterstrain technique and Contract Relax Stretching in reducing pain due to Piriformis syndrome. This research was conducted in the Kelurahan Pekapuran Raya of Banjarmasin City using a case study method with a visual analog scale (VAS) and Brief Pain Inventory Questionnaire (BPI). The results of the study are Strain Counterstrain and Contract Relax Stretching for 12 times therapy in 4 weeks can reduce pain disorders in the condition of Piriformis syndrome.